Melanocortin‐1 receptor (MC1R) genotypes do not correlate with size in two cohorts of medium‐to‐giant congenital melanocytic nevi. (20th May 2020) - Calbet‐Llopart, Neus; Pascini‐Garrigos, Mirella; Tell‐Martí, Gemma; Potrony, Miriam; Martins da Silva, Vanessa; Barreiro, Alicia; Puig, Susana; Captier, Guillaume; James, Isabelle; Degardin, Nathalie; Carrera, Cristina; Malvehy, Josep; et al.
Abstract: Congenital melanocytic nevi (CMN) are cutaneous malformations whose prevalence is inversely correlated with projected adult size. CMN are caused by somatic mutations, but epidemiological studies suggest that germline genetic factors may influence CMN development. In CMN patients from the U.K., genetic variants in MC1R, such as p.V92M and loss‐of‐function variants, have been previously associated with larger CMN. We analyzed the association of MC1R variants with CMN characteristics in two distinct cohorts of medium‐to‐giant CMN patients from Spain ( N = 113) and from France, Norway, Canada, and the United States ( N = 53), similar at the clinical and phenotypical level except for the number of nevi per patient. We found that the p.V92M or loss‐of‐function MC1R variants either alone or in combination did not correlate with CMN size, in contrast to the U.K. CMN patients. An additional case–control analysis with 259 unaffected Spanish individuals showed a higher frequency of MC1R compound heterozygous or homozygous variant genotypes in Spanish CMN patients compared to the control population (15.9% vs. 9.3%; p = .075). Altogether, this study suggests that MC1R variants are not associated with CMN size in these non‐UK cohorts. Additional studies are required to define the potential role of MC1R as a risk factor in CMN development.